Worksheets and Joyful Teaching Strategies in Teaching English to Students of English Village of Parit Baru - Aunurrahman, Aunurrahman; Sahrawi, Sahrawi; Hafis, Maliqul; Putra, Muhammad; Abdi Luhur, Amin; Wahyudiansyah, Muhammad (Universitas Pendidikan Ganesha, 2023)
English lessons are not compulsory in public elementary schools. It makes English a challenge for students in Indonesia's foreign language communication from an early age. This study aimed to find student worksheets and fun learning strategies, including singing and mentoring activities, to be implemented in teaching English to students. This research includes case study research. This study used a sampling technique to select five fifth-grade students who participated in this program. Data collection was carried out using participant observation techniques, and the documents included were student worksheets, photos, and activity videos. Data analysis techniques using thematic analysis techniques. The study results show that student worksheets and fun learning strategies can help students in English Village learn English through all teaching stages. It was concluded that alternative learning in the form of English Village using student worksheets and fun learning strategies had been proven to help students learn English by providing brief material that is clear and easy to understand.